2019
DOI: 10.1016/j.wsif.2019.102264
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the adoption of agricultural technology: The case of improved maize varieties in southern Ethiopia

Abstract: This study explores the role of gender-based decision-making in the adoption of improved maize varieties. The primary data were collected in 2018 from 560 farm households in Dawuro Zone, Ethiopia, and were comparatively analyzed across gender categories of households: male decision-making, female decision-making and joint decision-making, using a double-hurdle model. The results show that the intensity of improved maize varieties adopted on plots managed by male, female, and joint decision-making households ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 23 publications
(44 reference statements)
5
94
1
Order By: Relevance
“…In all sampled households, maize production takes place at the household level, and one or two family members (mostly husband, wife, or adult son(s)) within the household make maize production and consumption decisions either independently or jointly. As per the cultural norm of Dawuro community, a couple (wife and husband) of a household in the study area typically does not have separate maize farms (Gebre et al 2019a). In each household, the person most responsible for household food crop production (either husband, wife, or an adult son) was selected for the face-to-face interview.…”
Section: Data and Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In all sampled households, maize production takes place at the household level, and one or two family members (mostly husband, wife, or adult son(s)) within the household make maize production and consumption decisions either independently or jointly. As per the cultural norm of Dawuro community, a couple (wife and husband) of a household in the study area typically does not have separate maize farms (Gebre et al 2019a). In each household, the person most responsible for household food crop production (either husband, wife, or an adult son) was selected for the face-to-face interview.…”
Section: Data and Sampling Designmentioning
confidence: 99%
“…13 Principal Component Analysis is a dimensionality-reduction method that is often used to reduce the dimensionality of large data sets, by transforming a large set of variables into a smaller one which still contains most of the information of the large set. extension services for farmers in the areas of crop and livestock production and natural resource management (Gebre et al, 2019a).…”
Section: Data and Sampling Designmentioning
confidence: 99%
“…Among the existing improved varieties, BH660, BH540, and Pioneer hybrids dominate Ethiopia's seed market (Abate et al 2015). The major maize varieties used for production in Dawuro Zone are BH660, BH540, Pioneer hybrids, and local (recycled hybrids) varieties (Gebre et al 2019). Thus, this study included only these hybrids and local varieties.…”
Section: Maize Varieties In Ethiopiamentioning
confidence: 99%
“…The key determinants were that women heads of households were less educated and had weaker access to extension services, and thus tended to lack information about IMVs. Gebre et al [13] researched the adoption of IMVs in southern Ethiopia and found maize productivity in MHHs to be 44.3% higher than in female-headed households (FHHs). However, if FHHs were able to use their resources as effectively as MHHs, their productivity would increase by 42.3%.…”
Section: Gender and The Adoption Of Improved Maize And Wheat Varietiementioning
confidence: 99%
“…Furthermore, the authors differentiate de facto FHHs and de jure FHHs. The former benefit from a higher number of adult male family members to provide labor, more livestock, and smaller land size than the latter [13].…”
Section: Gender and The Adoption Of Improved Maize And Wheat Varietiementioning
confidence: 99%